EVALUATION OF TOPICAL MEDICATIONS, LAVAGE SOLUTIONS, AND LASER THERAPY FOR TREATING OPEN WOUNDS INDUCED IN BLUE-FRONTED AMAZON PARROTS, AMAZONA AESTIVA - Hippólito, Alícia Giolo [UNESP] (2019)
This study aimed to evaluate topical medications, lavage solutions and laser therapy for treating open clean wounds induced in captive blue-fronted Amazon parrots. Twenty-four blue-fronted Amazon parrots (Amazona aestiva) were divided into 6 groups according to the wound treatment: Group DEX—dexpanthenol 5% ointment; Group RIC—ointment of Ricinus communis oil; Group CHL—chlorhexidine digluconate solution 1%; Group SSS—0.9% sterile saline solution; Group LLL—low-level laser therapy and Group CON—no treatment, control. Four full-thickness wounds were induced in the front part of the chest area with the aid of an 8-mm punch. In each parrot, the 4 wounds received the same treatment, every 48 hours until healing, according to the group. In all groups, on postoperative days 5, 14 and 21, biopsies were taken for histological examination. One of the 4 wounds was not submitted to biopsy but rather was used for wound size measurements. Group CON presented the longest healing time and differed statistically from the other groups. Excluding Group CON, groups CHL and SSS showed no significant difference. Microscopically, groups DEX and CHL showed higher fibroplasia and epithelialization compared to the other groups on day 21. In conclusion, the best results were achieved macroscopically through lavage solutions, chlorhexidine digluconate solution or sterile saline solution; however, chlorhexidine digluconate was superior microscopically. The laser therapy and dexpanthenol ointment showed intermediate results, whereas the Ricinus communis oil showed the worst results.